Design of special vehicle condition monitoring system based on J1939. (June 2020) - Shao, Xuan; Kang, Xingwu; Wang, Xuping; Yuan, Xiaojing
Abstract: The special vehicle is one of the important equipment in China's military and aerospace fields, and its condition is closely related to the success of the mission. In view of the lack of real-time condition monitoring capability of special vehicles, a condition monitoring system based on J1939 protocol is designed in this paper. The system communicate with the Electronic Control Unit (ECU) in Controller Area Network (CAN) through the On Board Diagnostics (OBD) interface to obtain the real-time condition data of the vehicle and improve the active safety of the vehicle. The test results show that the system realizes the data exchange with the Electronic Control Unit (ECU), outputs the data to the personal computer (PC) through the serial port, realizes the protocol data visualization, and meets the expected design purpose.